Leninism, scientific socialism, and democracy - Pateman, Joe (2017)
During the twentieth century a number of accounts of Lenin’s theory and practice argued that Leninism is incompatible with democracy. In doing so, various scholars advanced the now popular belief, that the theory of scientific socialism defended by Lenin and prevalent in the Third International is undemocratic. Liberal and conservative critics of socialism are not the only proponents of this argument. Leninism has been criticised on this basis within the currents of Russian Bolshevism, Left Communism and Western Marxism. It is for this reason that the Marxism of Lenin and the Third International has been rejected as dogmatic, vulgar, and positivist: few contemporary Marxists condone dogmatism, vulgarity, or positivism. This dissertation examines and rejects the claim that Lenin’s theory of scientific socialism is anti-democratic. It argues that the Leninist conception of Marxism as a science is compatible with democratic practice, and promotes a democratic conception of socialism.